Model Project Based Learning Terhadap Kemampuan Menulis Puisi Pada Siswa Kelas VII SMPN 2 Sepatan Kabupaten Tangerang - Kamiri, Kamiri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine whether the effect of the project baset learning model on the ability to write poetry for class VII students of SMPN 2 Sepatan, Tangerang Regency. This research method is a quantitative method. The research sample was taken in 2 classes, the experimental class and the control class with 40 experimental class students and 40 control class students. The results of the study, from data analysis using the t-test the pooled variance medel t-test pretest experimental class and pretest control class obtained Ï a value of 0.02 which means that Ho is rejected, meaning that there is no difference in the experimental class pretest and the control class pretest, the experimental class posttest and the control class posttest are rejected, while H1 is accepted, meaning there is a difference between the experimental class posttest and the control class posttest using the model project base learning in writing poetry. Through the calculation data it can be concluded that there is an influence of the project baset learning model on the ability to write poetry. Keywords: Project Baset Learning, Poetry Writing, Ability